Médeia, a gyermekgyilkos az antik görög lélekfogalom tükrében - Bán, Katalin (Studia Litteraria, 2017)
The ancient Greek scholars and philosophers relished to use the deeds of Greek mythological figures as examples to demonstrate their theses, to analyse their motives and psychic processes in the soul. The Medea-myth, its psychology, the destructive emotion processes and their background factors in the woman’s soul have been interpreted by several scholars during antiquity in particular through the key lines of Euripides’ drama (1078–1080) to demonstrate their own philosophical theses. In the general Greek philosophical thinking, Medea remains the prototype of a cruel, dangerous, barbarian, occasionally regretful woman who embodies the paradigmatic exemplar of the disoriented psyche.